Compound based on DNA tetrahedron and preparation method and application thereof
Through functionalized DNA tetrahedral complex modified bioactive composite hydrogel scaffolds, efficient capture and fixation of endogenous BMP-2 is achieved, solving the problem of low capture efficiency in the prior art, and significantly accelerating bone Defect healing process.
Patent Information
- Application Number
- CN202411657009.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, the capture efficiency of BMP-2-binding peptides is not high, which makes it difficult to effectively locally enrich and fix endogenous BMP-2 during bone defect repair.
Using a functionalized DNA tetrahedral complex hydrogel scaffold modified, the efficient capture and fixation of BMP-2 is achieved through specific and high affinity binding to the BMP-2 binding peptide. The composite hydrogel scaffold was prepared by mixed curing of BMP-2-binding peptide-modified DNA tetrahedral complex, hydrogel monomer and photoinitiator.
The capture efficiency of endogenous BMP-2 was significantly improved, reaching 89.14%±4.24%, and targeted capture was achieved in the early stage of bone defects, promoting osteogenesis and differentiation of stem cells, thereby accelerating bone defect healing.
Smart Images

Figure CN119455134A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medicine, and in particular relates to a DNA tetrahedron-based complex and a preparation method and use thereof. Background Art
[0002] Bone tissue defects in the oral and maxillofacial region are a common clinical and social problem. The introduction of bone tissue engineering technology provides an effective and sustainable strategy for the repair and reconstruction of bone defects and is considered to be a promising treatment option to replace autologous bone transplantation. Bone tissue engineering promotes new bone formation through the interaction of scaffold materials, seed cells and growth factors. Among them, biomaterial-mediated exogenous stem cell transplantation and growth factor delivery systems are two widely studied bone tissue engineering programs. However, the former has been hindered in the translation of therapeutic applications due to social and ethical concerns. Because the latter plays a role in all stages of the bone defect repair process, current research focuses more on the application of growth factor delivery systems related to guided bone regeneration.
[0003] Bone morphogenetic protein-2 (BMP-2) is an important multifunctional growth factor that belongs to the transforming growth factor β (TGF-β) superfamily. BMP-2 can induce osteogenic differentiation of bone marrow mesenchymal stem cells and plays a key role in bone formation and regeneration. It is one of the bioactive molecules widely studied and applied in bone tissue engineering. At present, there are three main strategies for the application of BMP-2, namely, the delivery of soluble BMP-2, the delivery of exogenous BMP-2 based on bioactive carriers, and the enrichment of endogenous BMP-2 at the local bone defect site.
[0004] In response to the strategy of delivering soluble BMP-2, recombinant human BMP-2 (rhBMP-2) injection was developed. However, due to the poor in vivo stability and easy diffusion of soluble BMP-2, supraphysiological concentrations and systemic administration are required to achieve the desired effect. Furthermore, exogenous BMP-2 delivery systems based on a variety of bioactive carriers have been widely studied and applied. This strategy can achieve co-localization and local release of BMP-2 in locally damaged bone tissue. However, treatment based on the delivery of exogenous BMP-2 also faces some challenges, including technical difficulties such as uncontrollable release, low integration rate, protein denaturation during integration, ectopic bone formation, radiculitis, vertebral osteolysis, and easy complications such as fractures, as well as high cost. In order to overcome these obstacles, the study proposed a strategy to use endogenous BMP-2 to promote local bone healing of defects. At the bone defect, BMP-2 can be synthesized and released into the bone matrix, then enter the systemic circulation, and cannot be enriched locally. Therefore, in order to promote the healing of bone defects, local enrichment and fixation of endogenous BMP-2 is required. Studies have found that a BMP-2 binding peptide (BBP) composed of 9 amino acids can specifically bind to BMP-2. Compared with the application of anti-BMP-2 antibodies, BBP shows more stability, higher selective affinity and lower price.
[0005] The document (DOI: 10.1177 / 0363546518787507) discloses a method of covalently fixing BBPs (more than one BMP-2 binding peptide) to a polycaprolactone (PCL) membrane to capture endogenous BMP-2. However, the efficiency of capturing BMP-2 is not high.
[0006] The strategy of enriching endogenous BMP-2 based on specific binding to BBP has the problem of low capture efficiency. It is of great significance to develop a method that can improve the capture efficiency of endogenous BMP-2. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the object of the present invention is to provide a DNA tetrahedron-based complex and a preparation method and use thereof.
[0008] The invention provides a composite hydrogel, which is obtained by mixing and solidifying a DNA tetrahedron complex modified by a BMP-2 binding peptide, a hydrogel monomer and a photoinitiator.
[0009] Furthermore, the mass of the hydrogel monomer accounts for 0.5-1.5wt.% of the total mass of the BMP-2 binding peptide modified DNA tetrahedral complex and the hydrogel monomer; the molar ratio of the BMP-2 binding peptide modified DNA tetrahedral complex to the photoinitiator is 1:200-300×103 .
[0010] Furthermore, the mass of the hydrogel monomer accounts for 1wt.% of the total mass of the BMP-2 binding peptide modified DNA tetrahedral complex and the hydrogel monomer; the molar ratio of the BMP-2 binding peptide modified DNA tetrahedral complex to the photoinitiator is 1:255×10 3 .
[0011] Furthermore, in the BMP-2 binding peptide-modified DNA tetrahedron complex, the BMP-2 binding peptide modifies 1 to 3 single strands in the DNA tetrahedron.
[0012] Furthermore, in the BMP-2 binding peptide-modified DNA tetrahedron complex, the BMP-2 binding peptide modifies three single strands in the DNA tetrahedron.
[0013] Furthermore, the BMP-2 binding peptide-modified DNA tetrahedral complex is self-assembled from SH-S1, bS2, bS3, bS4, and b*-BBP single chains; SH-S1 is a thiol-modified S1 single chain, b*-BBP is a propargyl-modified BBP, and the reaction with an azide-modified sticky end under the action of a catalyst is purified to obtain; the S1 sequence is shown in SEQ ID NO.2, and the sequences of bS2, bS3, bS4, BBP, and the sticky end are shown in SEQ ID NO.6, SEQ ID NO.7, SEQ ID NO.8, SEQ ID NO.1, and SEQID NO.9, respectively.
[0014] Furthermore, the molar ratio of the propargyl-modified BBP to the azide-modified sticky end is 1:1, and the catalyst is a monovalent copper ion catalyst.
[0015] Furthermore, the hydrogel monomer is methacrylated hyaluronic acid; and the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.
[0016] Furthermore, the methacrylated hyaluronic acid is prepared using methacrylic anhydride and hyaluronic acid as raw materials, and the mass ratio of the methacrylic anhydride to the hyaluronic acid is 6 to 10:5, preferably 8.32:5.
[0017] The present invention also provides a method for preparing the composite hydrogel, which comprises the following steps: mixing the DNA tetrahedron complex modified by the BMP-2 binding peptide, the hydrogel monomer and the photoinitiator, and curing to obtain the composite hydrogel.
[0018] Furthermore, the curing wavelength is 350-400 nm, preferably 365 nm; the curing time is 20-40 seconds, preferably 30 seconds.
[0019] The present invention also provides use of the composite hydrogel in preparing a biological scaffold material for repairing bone defects.
[0020] The present invention has achieved the following beneficial effects:
[0021] The present invention designs a bioactive composite hydrogel scaffold modified with a functionalized DNA tetrahedral complex containing BMP-2, stably combines a functionalized BMP-2 binding peptide with a tetrahedral framework structure having a unique three-dimensional spatial structure and refined programmability by chemical clicking, and then further prepares a composite hydrogel scaffold with methacryloyl hyaluronic acid (HAMA). A strategy for fixing BMP-2 by specifically and highly affinity binding with a BMP-2 binding peptide is proposed, and the performance of the functionalized DNA tetrahedral complex in efficiently capturing BMP-2 in an ordered and stable topological spatial conformation is achieved. The functionalized composite hydrogel scaffold achieves targeted capture of endogenous BMP-2 in the early stage of bone defects and stimulates osteogenic differentiation of stem cells to promote in situ osteogenesis, avoiding the occurrence of a series of complications caused by the delivery of exogenous bone morphogenetic protein-2, poor in vivo stability, safety issues and high cost issues, and has good application prospects.
[0022] The present invention successfully chemically connects the BMP-2 binding peptide to a single-stranded DNA of a specific sequence, and further synthesizes a stable functionalized DNA tetrahedral framework structure (p3T) and its corresponding composite hydrogel scaffold (HA-p3T), which significantly improves the capture efficiency of rhBMP-2 and achieves unexpected technical effects. Moreover, compared with the literature (DOI: 10.1177 / 0363546518787507), the capture efficiency of the HA-p3T of the present invention is as high as 89.14% ± 4.24%, and the capture efficiency is significantly improved.
[0023] Among them, the certain mechanical strength of HAMA and its chemical connection form with the functionalized DNA tetrahedral framework structure are conducive to the scaffold to stably achieve biological efficacy; the high affinity and specific binding of BBP to human recombinant BMP-2 (rhBMP-2), and the topological spatial conformation of trivalent ligand binding provided by p3T help the HA-p3T scaffold to efficiently capture and fix BMP-2 in vitro and in vivo. The capture system constructed by the present invention can continuously release effective BMP-2 components in the culture environment of bone marrow mesenchymal stem cells (BMSCs), promote the osteogenic differentiation of BMSCs, and significantly upregulate the expression of osteogenic differentiation-specific proteins and genes. The biological scaffold material HA-p3T with p3T functionalization can achieve specific and large-scale capture of endogenous BMP-2 in the early stage of bone defect, which is expected to promote early bone formation and accelerate bone defect healing. The HA-p3T scaffold with the ability to specifically capture endogenous BMP-2 can efficiently promote bone regeneration and reconstruction, and finally accelerate the bone healing process after bone defect, confirming that HA-p3T is a better candidate for potential clinical application in bone defect repair.
[0024] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0025] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1: Preparation, verification and characterization of functionalized DNA tetrahedral framework (BBPs-tFNA). (A) Schematic diagram of the preparation process of B*-BBP and p3T. (B) The successful step-by-step synthesis of T and p3T was verified by polyacrylamide gel electrophoresis (PAGE). (C) The successful preparation of T and p3T was confirmed by high-performance capillary electrophoresis (HPCE). (D) PAGE results show the size of synthesized T, p1T, p2T, and p3T, as well as the results of relative fluorescence intensity, respectively, when S1 was labeled with cy5 (red) and BBPs were labeled with FITC (green). ns: no statistical difference. (E) Particle size of tFNA and p3T. (F) Potential of tFNA and p3T. (G) Transmission electron microscopy (TEM) image of p3T. (H) Atomic force microscopy (AFM) image of p3T. (I) Enzyme stability of p3T treated with 1U / ml DNase I (0, 1, 3, 6, 9, 12, 24, 48 hours). (J) Stability of p3T in 10% fetal bovine serum (FBS) (0, 1, 3, 6, 9, 12, 24 and 48 hours). (K) Stability of p3T in 5% FBS (0, 1, 3, 6, 9, 12, 24 and 48 hours). (L) Storage stability of p3T at room temperature for 7 days. In (I)-(L), Gelred and cy5-labeled S1 were displayed with green and red fluorescence, respectively, and their relative fluorescence intensities were calculated. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0027] Figure 2:Synthesis and characterization of BBPs-tFNA modified HAMA scaffold. (A) Schematic diagram of the preparation of the composite hydrogel scaffold HA-p3T. (B) Scanning electron microscopy (SEM) image of HA-p3T. (C) Rheological and compression properties of HA-p3T, stress-time curve (i), stress-strain curve (ii), stress-ω curve (iii) and stress-temperature curve (iv), respectively. G' and G" are the storage modulus and loss modulus, respectively. (D) Nuclear magnetic resonance (NMR) results reveal the chemical shifts of hydrogen bonds in HA and HA-p3T. (E) Water contact angle measurements show the difference in surface wettability between HA and HA-p3T. ****P<0.0001. (F) The carbon element spectrum was determined by X-ray photoelectron spectroscopy (XPS), and the full spectrum was scanned for HA-p3T (i), and the partial spectrum was scanned for HA and HA-p3T (ii&iii), respectively. (G) Fluorescence images and detection results show , elution of BBPs physically adsorbed on HAMA, BBPs were labeled with FITC (green fluorescence). *P<0.05, **P<0.01, ***P<0.001, ****P<0.0001. (H) Fluorescence images and detection results show the elution of BBPs after chemical attachment of p1T, p2T and p3T to HAMA, BBPs were labeled with FITC (green fluorescence). ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0028] Figure 3: The efficiency of BBPs-tFNA functionalized HAMA in enriching BMP-2. (A) PAGE results show the elution band spectra of T, p1T, p2T, and p3T after binding with equal concentrations of rhBMP-2 and FBS, and the quantitative statistics of the band signals showing the capture efficiency of BMP-2 and FBS. (B) Fluorescence images show the elution of reGFP with green signals after incubation with HA and HA-p3T, respectively, and the corresponding relative fluorescence intensity statistics were performed. p3T was labeled with Cy5 (red). (C) Fluorescence images and immunofluorescence quantitative analysis of BMP-2 fixed on HA and HA-p3T scaffolds. (D) The amount and efficiency of BMP-2 captured by each composite hydrogel scaffold. (E) Fluorescence quantification results of HAMA-modified 3pS (3BBP-ssDNA) and p3T (3BBP-tFNA) at various concentrations (i); the amount and efficiency of BMP-2 captured by HA-3pS and HA-p3T at equal concentrations (ii). (F) The effect of various BMP-2 concentrations on the efficiency of HA-p3T in capturing BMP-2. (G) Release curve of BMP-2 captured by HA-p3T in 10% FBS. *P<0.05, **P<0.01, ***P<0.001, ****P<0.0001. ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0029] Figure 4 :Verification of the biological activity of BMP-2 enriched in HA-p3T scaffolds. (A) The cell activity and proliferation of bone marrow mesenchymal stem cells (BMSCs) treated with each hydrogel scaffold were determined by CCK-8 assay. (B) Live / dead staining of BMSCs after treatment with each hydrogel scaffold. Scale bar: 200μm. (C) Fluorescence quantification results of live and dead cells. (D) ALP staining was used to detect the effects of the control group and different treatment groups (BMP-2, HA+BMP-2, HA, HA-T+BMP-2, HA-T, HA-T+BMP-2, HA-p3T) on the osteogenic activity of BMSCs. Scale bar: 400μm (magnification 10 times). Scale bar: 200μm (magnification 20 times). (E) Quantitative detection of ALP enzyme activity. (F) Alizarin red staining showed the calcium nodules formed by BMSCs under different treatment groups. Scale bar: 500μm. (G) Semi-quantitative mineralization level detection of calcium nodules. (H) Statistical analysis of the expression levels of osteogenic genes (ALP, Runx2, BSP, OSX, OPN) by RT-qPCR results. (I) Schematic diagram of the effect of BMP-2 on BMSCs captured by HA-p3T. *P<0.05, **P<0.01, ***P<0.001, ****P<0.0001. ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0030] Figure 5 :Confirmation of BMP-2 retention of osteogenic activity on HA-p3T scaffolds. (A) Western blot results of osteogenic differentiation-related proteins (ALP, Runx2, OSX, OPN) after BMSCs were treated with each group (Control, HA, HA-T, HA-T, BMP-2). (B) Quantitative statistics of Western blot results. (CF) Immunofluorescence staining of osteogenic differentiation-related proteins (ALP, Runx2, OSX, OPN) after treatment in each group. Scale bar: 40μm. (G) Quantitative analysis of the relative fluorescence intensity of ALP, Runx2, OSX, and OPN. *P<0.05, **P<0.01, ***P<0.001, ****P<0.0001. ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0031] Figure 6 : The efficiency of HA-p3T scaffold in capturing endogenous BMP-2. (A) Schematic diagram of rat skull defect model construction and application of hydrogel materials in local bone defect repair process. (B) In vivo imaging results of HA-ss (ssDNA-modified HAMA) and HA-p3T implanted in rats within 10 days. All materials were labeled with Cy5 fluorescence. (C) Capture curve results show the capture of endogenous BMP-2 in local bone defects by each group (shame group, control group, HA, HA-p3T). #p<0.0001, n=4. (D) Quantitative statistics of BMP-2 captured by each group of materials on the 7th day (n=4). (E) Immunofluorescence staining of BMP-2 captured by each group of materials after 1 week of bone defect. Scale bar: 250μm. Scale bar of magnified area: 60μm. (F) Statistical analysis of relative fluorescence intensity of captured BMP-2 (n=6). (G) Immunohistochemistry showed the expression of BMP-2 around the defect 2 weeks after bone defect. Scale bar: 600 μm. Scale bar of magnified area: 150 μm. (H) Statistical analysis of the relative positive area captured by BMP-2 (n=6). ****p<0.0001. ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD).
[0032] Figure 7HA-p3T captures endogenous BMP-2 to promote bone remodeling. (A) Micro-CT scans and three-dimensional reconstruction of the skull defect at 1 and 2 months. (B) Statistical analysis of bone density (BMD, i), bone volume / total volume (BV / TV, ii), trabecular number (Tb.N, iii), and trabecular thickness (Tb.Th, iv) (n=6) at the bone defect site. (C, D) HE and Masson staining. Scale bar: 500μm. Scale bar for magnified area: 50μm. The black solid line of the double arrow indicates the range of the bone defect. (E, F) Immunofluorescence staining of Col-I and Runx2 in the bone defect and surrounding tissues. Scale bar: 500μm. Scale bar for magnified area: 50μm. The white dotted line of the double arrow indicates the range of the bone defect. (G) Immunohistochemical staining image of OCN in the bone defect and surrounding tissues. Scale bar: 500μm. Magnified area scale bar: 50 μm. The black solid line with double arrows indicates the range of bone defects. (H) Fluorescence quantification of Col-I (i) and Runx2 (ii) immunofluorescence assay (n=6). (I) Statistical analysis of relative protein expression of OCN (n=6). (J) Quantitative analysis of trabecular spacing (Tb.Sp) (n=6). ****p<0.0001. ns: no statistical difference. All experiments were repeated at least 3 times, and the data are expressed as mean ± standard deviation (SD). DETAILED DESCRIPTION
[0033] The raw materials and equipment used in the present invention are all known products, which are obtained by purchasing commercially available products.
[0034] Materials and reagents: All DNA sequences or functionalized DNA sequences were synthesized, labeled, and purified by Shanghai Shenggong Biotechnology Co., Ltd. The company also provided TCEP Tris-(2-carboxyethyl)-phosphochloridate. The culture media used included α-minimal essential medium (α-MEM), penicillin-streptomycin, fetal bovine serum (FBS), trypsin-EDTA, and phosphate-buffered saline (PBS; SH30256), all of which were purchased from Hyclone Laboratories, Inc. Polyformaldehyde was purchased from Biosharp Life Sciences. Hyaluronidase and EDTA decalcification solution were purchased from Servicebio. Gelred nucleic acid dye was provided by Beijing Solebow Technology Co., Ltd. Alkaline phosphatase staining kit, Alizarin Red S staining kit, 10×TBE, 50×TAE, and Calcein / PI cell viability and cytotoxicity detection kit (Beyotime, C2015S) were all purchased from Biodi Biotechnology. Human recombinant BMP-2 (rhBMP-2) solution, RT-qPCR kit, TRIzol, etc. were provided by ThermoFisher Scientific. 488 secondary antibodies, Alexa 594 secondary antibody, Alexa 561 secondary antibodies were purchased from Sigma-Aldrich Merck. Photoinitiator lithium phenolphthalein diacetate (LAP) was purchased from Suzhou Yongqunquan Intelligent Equipment Co., Ltd.
[0035] TM buffer: 50 mM magnesium chloride, 20 mM Tris(hydroxymethyl)aminomethane, pH adjusted to 8.0. Polyacrylamide gel electrophoresis (PAGE) buffer: 1×TBE, composed of: 1 mM ethylenediaminetetraacetic acid disodium salt (EDTA), 12.5 mM magnesium acetate, 40 mM Tris(hydroxymethyl)aminomethane, 40 mM boric acid, pH adjusted to 8.0. Binding buffer: (10 mM MgCl2 in DPBS, pH=7.4).
[0036] In the embodiments and experimental examples of the present invention, the modified or unmodified single-stranded DNA sequences and polypeptide-related amino acid series involved are as follows:
[0037] The amino acid sequence of BBP (SEQ ID NO.1) is as follows:
[0038] KGYPVHP
[0039] The sequence of BBP-pra modified with propargylglycine (pra) at the lysine end of BBP is as follows:
[0040] propargylglycine-KGYPVHPST
[0041] The nucleotide sequences of the four single-stranded DNAs are as follows:
[0042] S1 (SEQ ID NO. 2):
[0043] ATTTATCACCCGCCATAGTAGACGTATCACCAGGCAGTTGAGACG AAATTCCTAAGTCTGAA;
[0044] S2 (SEQ ID NO.3):
[0045] ACATGCGAGGGTCCAATACCGACGATTACAGCTTGCTACACGATT CAGACTTAGGAATGTTCG;
[0046] S3 (SEQ ID NO.4):
[0047] ACTACTATGGCGGGTGATAAAACGTGTAGCAAGCTGTAATCGACG GGAAGAGCATGCCCATCC;
[0048] S4 (SEQ ID NO.5):
[0049] ACGGTATTGGACCCTCGCATGACTCAACTGCCTGGTGATACGAGG ATGGGCATGCTCTTCCCG;
[0050] Among them, the 5' end of S1 used to prepare the thiol-functionalized DNA tetrahedral framework structure is chemically connected with a thiol group (SHC6, which is a n-hexylthiol group):
[0051] SH-S1:
[0052] 5'-SHC6-ATTTATCACCCGCCATAGTAGACGTATCACCAGGCAGTTGAGACGAACATTCCTAAGTCTGAA-3';
[0053] S2-S4 is connected by complementary binding of the sticky ends bb*. After the nucleic acid adaptor is connected to the sticky ends, the nucleotide sequence of bS2-bS4 is as follows:
[0054] bS2 (SEQ ID NO.6):
[0055] ACCCAACAACCACATGCGAGGGTCCAATACCGACGATTACAGCTTGCTACACGATTCAGACTTAGGAATGTTCG;
[0056] bS3 (SEQ ID NO.7):
[0057] ACCCAACAACCACTACTATGGCGGGTGATAAAACGTGTAGCAAGCTGTAATCGACGGGAAGAGCATGCCCATCC;
[0058] bS4 (SEQ ID NO.8):
[0059] ACCCAACAACCACGGTATTGGACCCTCGCATGACTCAACTGCCTGGTGATACGAGGATGGGCATGCTCTTCCCG;
[0060] The nucleotide sequence of the sticky end b*-N3) modified by azide (N3) and the polypeptide BBP connected to the sticky end b*-BBP is as follows, wherein the nucleotide sequence of the sticky end (SEQ ID NO.9) is GGTTGTTGGGT:
[0061] b*-N3: 5'-GGTTGTTGGGT-N3-3'
[0062] b*-BBP:5'-GGTTGTTGGGT-BBP-3'
[0063] The "room temperature" referred to in the present invention means 25±10°C, and "overnight" means 12±5 hours.
[0064] Example 1: Construction of a functionalized DNA tetrahedral framework
[0065] First, BBP-pra and b*-N3 were chemically click-linked at a molar ratio of 1:1 under the catalysis of monovalent copper ions, and b*-BBP was further purified.
[0066] SH-S1, S2, S3, bS4, and b*-BBP single-chain systems were prepared at a concentration of 1 μM, respectively. 1 μL of each single chain was added to 95 μL TM buffer, mixed thoroughly, and synthesized by a one-step method (95°C for 10 minutes, then cooled to 4°C for 20 minutes), and stored at 4°C to obtain a functionalized DNA tetrahedral framework structure (named p1T), which was modified with 1 BBP polypeptide.
[0067] Example 2: Construction of a functionalized DNA tetrahedral framework
[0068] The method of Example 1 was used with reference to the above, except that 1 μL of SH-S1, S2, bS3, bS4 single chains and 2 μL of b*-BBP were added to 94 μL of TM buffer to obtain a functionalized DNA tetrahedral framework structure (named p2T) modified with two BBP polypeptides.
[0069] Example 3: Construction of a functionalized DNA tetrahedral framework
[0070] The method of Example 1 was used with the exception that 1 μL of SH-S1, bS2, bS3, bS4 single chains and 3 μL of b*-BBP were added to 93 μL of TM buffer to obtain a functionalized DNA tetrahedral framework structure (named p3T) modified with three BBP polypeptides ( Figure 1 A).
[0071] Example 4: Construction of composite hydrogel scaffold
[0072] The composite hydrogel was prepared by the following method:
[0073] 5 g of hyaluronic acid (MW = 94 wDa) and 8.32 g of methacrylic anhydride were dissolved in 50 mL of deionized water. The pH of the mixture was adjusted to 8.0 using NaOH. The solution was stirred continuously overnight on ice. Afterwards, all reaction solutions were dialyzed for 3 days, and the dried products were collected by freeze drying to obtain methacryloyl hyaluronic acid (HAMA).
[0074] The functionalized DNA tetrahedral framework structure (p1T, 1 μM) prepared in Example 1 was mixed with HAMA to obtain a mixture (containing 1 wt.% HAMA). For every 100 μL of the mixture, 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM) was added. The mixture was then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, it was washed three times with TM buffer (10 mM Tris-HCl, 10 mM MgCl2, pH = 8.0) to remove any unreacted materials. The prepared sample was recorded as HA-p1T.
[0075] Example 5: Construction of composite hydrogel scaffold
[0076] The method of Example 4 was used with reference to the above, except that p1T was replaced by p2T. The prepared sample was designated as HA-p2T.
[0077] Example 6: Construction of composite hydrogel scaffold
[0078] The method of Example 4 was used with reference to the above, except that p1T was replaced by p3T. The prepared sample was designated as HA-p3T.
[0079] The following is the preparation of control products by means of control examples.
[0080] Comparative Example 1: Preparation of non-functionalized DNA tetrahedral framework structure
[0081] Quantitative SH-S1, S2, S3, and S4 were prepared as a 1 μM system. 1 μL of each single strand was added to 96 μL TM buffer, mixed thoroughly, and synthesized by a one-step method (95°C for 10 minutes and then cooled to 4°C for 20 minutes), and stored at 4°C to obtain a non-functionalized DNA tetrahedral framework structure (named T), which was not modified with the BBP polypeptide.
[0082] Comparative Example 2: Construction of HA-T composite hydrogel scaffold
[0083] The method of reference example 4 was different only in that p1T was replaced by T. The prepared sample was recorded as HA-T.
[0084] Comparative Example 3: Preparation of HA
[0085] HAMA was dissolved in TM buffer at a concentration of 1% wt to obtain a HAMA solution. For every 100 μL of HAMA solution, 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM) was added. The mixture was then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, it was washed three times with TM buffer ((10 mM Tris-HCl, 10 mM MgCl2, pH = 8.0)) to remove any unreacted material, and the resulting hydrogel was named HA.
[0086] Control Example 4: Preparation of HA-3pS
[0087] Preparation of SH-ssDNA-BBP: bS2-SH (the 3' end of the bS2 described above with a modified SH bond) and the b*-BBP synthesized above were synthesized in a ratio of 1:1 to form BBP-S2-SH (expressed as SH-ssDNA-BBP).
[0088] HA-3pS: SH-ssDNA-BBP (3 μM) was mixed with 1% HAMA. For every 100 μL of the mixture, 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM) was added. The mixture was then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, it was washed three times with TM buffer (10 mM Tris-HCl, 10 mM MgCl2, pH = 8.0) to remove any unreacted material, and the resulting hydrogel was named HA-3pS.
[0089] The following experimental examples demonstrate the beneficial effects of the present invention. The samples used in the following experiments were prepared according to the methods of the above embodiments or control examples.
[0090] Experimental Example 1: Structural Characterization and Performance Testing
[0091] 1. Experimental Methods
[0092] 1. Synthesis and characterization of functionalized DNA tetrahedral framework (BBPs-tFNA)
[0093] 1.1 Synthesize functionalized tFNA capture structures, and combine characterization methods such as atomic force microscopy, transmission electron microscopy, gel electrophoresis, and capillary electrophoresis to clarify the structural chemical properties such as yield and stability of tFNA structures of different scales and design details.
[0094] 1.2 Serum, enzyme, and storage stability of the functionalized DNA tetrahedral framework structure (p3T): First, the p3T structure was labeled with Cy5 and its stability was determined under different reaction conditions (10% FBS, 5% FBS, 1U / mL DNase I), different incubation environments (37°C, room temperature, 4°C), and different reaction times (0-48h, 0-7d). The resulting product was detected by 2% agarose gel staining (AGE) in 0.5xTAE buffer, detected using an electrophoresis instrument (Bio-Rad), and visualized using a gel-blot imaging system (ibright FL 1500, Thermo Fisher Scientific).
[0095] 2. Synthesis and characterization of BBPs-tFNA modified HAMA scaffold
[0096] 2.1 BBPs-tFNA was modified on HAMA scaffolds in the above manner to obtain complexes HA-p1T, HA-p2T, and HA-p3T for BMP-2 enrichment. The surface morphology was observed by scanning electron microscopy (SEM).
[0097] 2.2 Mechanical properties of HA-p3T scaffolds: The Young's modulus was tested using an MCR 302e rheometer (Anton Paar), and the stress-time curve, stress-strain curve, stress-ω curve, and stress-temperature curve were obtained.
[0098] 2.3 Detection and verification of the chemical modification of the HA-p3T scaffold: The chemical shifts of hydrogen bonds in HA and HA-p3T were detected using an Avance NMR spectrometer (Bruker); the differences in the composition and chemical bonds of HA and HA-p3T were measured using a K-Alpha x-ray photoelectron spectrometer (XPS) system (Thermo Fisher Scientific).
[0099] 2.4 Determination of surface wettability: The wettability of the surfaces of HA and HA-p3T scaffolds was determined by a contact angle tester (JC2000D2H), and the contact angles were measured and calculated by Drop analysis software.
[0100] 3. Efficacy verification of BBPs-tFNA functionalized HAMA enriched with BMP-2
[0101] 3.1 The affinity and specificity of BBPs-tFNA functionalized HAMA binding to BMP-2 were detected by PAGE experiment.
[0102] 3.2 The BMP-2 content retained on the HA-p3T scaffold was indirectly detected by immunofluorescence.
[0103] Treatment of HA-p3T scaffolds: Incubate the scaffolds with 1 μg / mL rhBMP-2 in PBS with gentle shaking for 1 hour. Then rinse with PBS solution 3 times (10 minutes each time), then block the scaffolds with PBS containing 1% (w / v) bovine serum albumin (BSA) for 1 hour and repeat the above rinsing process. Incubate the scaffolds with 2 μg / mL primary antibody (Rabbit Anti-BMP2 antibody, Bioss) in blocking solution with gentle shaking for 1 hour. After washing as above, add 8 μg / mL secondary antibody (goat anti-rabbit Alexa Fluor 488, Invitgen) and incubate in the same way for 0.5-1 hour and then wash again. After sufficient drying, detect and analyze using a fluorescence microscope.
[0104] 3.3 The ELISA test was used to perform in vitro quantitative detection of BMP-2 captured on the composite hydrogel scaffolds (HA, HA-T, HA-p1T, HA-p2T, HA-p3T) to quantify the material's BMP-2 capture efficiency and the amount released in 10% FBS.
[0105] Treatment of the composite hydrogel scaffold: The composite hydrogel scaffold was incubated with 500 μL of 1 μg / mL rhBMP-2 in PBS with gentle stirring for 1 hour. The supernatant of each group was then collected and washed 3 times with PBS solution (10 minutes each time) to remove the unbound residual rhBMP-2. The washing solution of each group was mixed with the supernatant collected in the previous step. According to the instructions of the reagent manufacturer, the amount of unbound rhBMP-2 was detected and analyzed using a BMP-2 ELISA kit (Elabscience Biotechnology). The amount of immobilized rhBMP-2 on the composite hydrogel scaffold and the capture efficiency were calculated based on the difference between the original incubation solution and the unbound rhBMP-2.
[0106] 4. Bioactivity Verification of BMP-2 Enriched in HA-p3T Scaffold
[0107] 4.1 Experimental operations involving animal surgery were performed according to the requirements of the ethics committee. The present invention extracted rat bone marrow mesenchymal stem cells (BMSCs) from the long bone marrow of 2-week-old SD rats to study cell proliferation and differentiation and evaluate the biocompatibility of hydrogel scaffold materials.
[0108] 4.2 The effect of each group of hydrogel scaffold materials on the proliferation of BMSCs was evaluated by CCK-8 experiment, and the living cells and dead cells on the hydrogel scaffold materials were immunofluorescently stained. The cell distribution on the hydrogel scaffold was observed under confocal laser scanning microscopy (CLSM) and statistical analysis was performed.
[0109] 4.3 ALP staining and ALP enzyme activity detection: Consistent with the above pretreatment of the materials, 500 μL of 1 μg / mL rhBMP-2 was incubated with the composite hydrogel scaffold in PBS for 1 hour and then washed with PBS three times, each time for 10 minutes. 4 After being inoculated in a 24-well plate at a density of 1.54 × 10 / cm2 and cultured overnight, a composite hydrogel scaffold was used on a tissue culture plate insert (Labselect) to act on the BMSCs culture system. After 7 days of co-culture, the adherent cells were fixed with 4% paraformaldehyde. ALP was stained and observed using the BCIP / NBT kit (Beyotime) and the ALP content was qualitatively detected. At the same time, the above-mentioned BMSCs were lysed, and the ALP activity of each group was quantitatively determined using the ALP enzyme activity detection kit (Beyotime). The measured ALP activity was normalized to the total protein content according to the indication of the alkaline phosphatase activity unit.
[0110] 4.4 Alizarin red staining and semi-quantitative analysis of calcium nodules: The rat BMSCs osteogenic differentiation kit (OriCell) was used to detect the effect of HA-p3T scaffold material pretreated with rhBMP-2 on the osteogenic differentiation ability of BMSCs. BMSCs were treated in the same conditions as above, and rat BMSCs complete culture medium was used instead of α-culture medium to induce osteogenic differentiation in different treatment groups. Alizarin red staining experiment was performed after 15 days of cultivation, and the red-stained calcium nodules were observed under a microscope and images were obtained. Cetylpyridinium chloride (CPC) was used to semi-quantitatively analyze the mineralized nodules formed under the cultivation conditions of each group.
[0111] 5. Confirmation of BMP-2 osteogenic activity on HA-p3T scaffolds
[0112] Detection of osteogenic gene expression: BMSCs were cultured under the same conditions as the above-mentioned treatment of the composite materials, and the expression levels of the corresponding early osteogenic (ALP, Runx2, OSX) and mid-late osteogenic genes (BSP, OPN) were detected by real-time quantitative polymerase chain reaction (RT-qPCR) at 1 week and 2 weeks of treatment, respectively.
[0113] Subsequently, Western Blot (WB) and cell immunofluorescence techniques were used to detect the expression levels of the corresponding osteoblast-related proteins (ALP (anti-ALP antibody, ET1601-21), Runx2 (anti-Runx2 antibody, ET1612-47), OSX (anti-OSX antibody, ER1914-47), and OPN (anti-OPN antibody, 22952-1-AP)).
[0114] 6. Validation of the efficacy of HA-p3T scaffold in capturing endogenous BMP-2
[0115] 6.1 Use in vivo imaging technology to continuously monitor the retention of active ingredients in subcutaneously implanted HA-p3T (BBP-tFNA-modified HAMA) and HA-ss (BBP-ssDNA-modified HAMA) hydrogel scaffolds.
[0116] 6.2 Construction of rat skull defect model: First, 6-week-old rats were randomly divided into 4 groups, including a blank control group (Sham group), a control group (Control group), a HA group and a HA-p3T group. After exposing the rat skull, a circular defect with a diameter of 4 mm was created on both sides of the midline using an electric drill of specified size. Subsequently, under ultraviolet light irradiation for 20 seconds, the hydrogel materials of each group were pre-cured into scaffold materials of corresponding sizes using a mold, and the adapted materials were placed low in the defect. Finally, the mucoperiosteum and skin tissues were tightly sutured in turn. All rats received continuous injections of penicillin for 3 days to prevent infection.
[0117] 6.3 Test the capture efficiency of composite hydrogel scaffolds for endogenous BMP-2: First, the capture amount of endogenous BMP-2 by each group of hydrogel scaffolds in the bone defect was quantitatively detected to obtain the capture curves (n=4) at 1 day, 3 days, 5 days, 7 days, 10 days and 14 days after surgery. Then, based on the results of the quantitative detection of the above capture curves, the defect tissues on the 7th and 14th days were subjected to immunofluorescence staining and immunohistochemistry experiments to verify the BMP-2 content in the tissues around the bone defects of each group (n=6).
[0118] 7. Verification of the effect of HA-p3T in capturing endogenous BMP-2 and promoting bone remodeling
[0119] 7.1 Three-dimensional detection of long-term osteogenic efficacy in each group: At 1 month and 2 months after surgery, the skull defect sites of rats in each group were scanned and 3D reconstructed using Micro CT (TD-273 Micro CT 50 / 100 Version 1.3). Furthermore, the results of Micro CT were quantitatively analyzed using SCANCO medical evaluation software to evaluate the new bone formation in the skull defect sites of each group (n=6), and the bone volume / total volume (BV / TV), bone mineral density (BMD), trabecular thickness (Tb.Th), total number of trabeculae (Tb.N) and trabecular spacing (Tb.Sp) were analyzed.
[0120] 7.2 Histology, tissue immunofluorescence staining and immunohistochemistry evaluation: Rat skull samples were immersed in formalin-ethylenediaminetetraacetic acid (EDTA) solution for decalcification, and the decalcification solution was changed every other day until the fourth week. They were then paraffin-embedded and sectioned. HE and Masson staining were performed respectively, and the degree of tissue repair was analyzed by microscopic scanning.
[0121] Subsequently, tissue immunofluorescence staining was used to detect the relative expression level of OCN (anti-OCN antibody, GB11233) in the bone tissue of each group to evaluate the long-term osteogenesis ability. Immunohistochemistry was used to evaluate the relative expression levels of Col-I (anti-Col-I antibody, GB11022-3) and Runx2 (anti-Runx2 antibody, bs-1134R) to further evaluate the collagen expression and osteogenesis effect of each group. The specimen results were observed using a tissue section scanner, and the data were analyzed using ImageJ analysis software.
[0122] 2. Experimental Results
[0123] 1. Characterization of BBPs-tFNA
[0124] Figure 1 A is a schematic diagram of the preparation of the functionalized DNA tetrahedral framework (p3T).
[0125] The successful and efficient step-by-step synthesis of BBPs and tFNA was verified by polyacrylamide gel electrophoresis (PAGE). Figure 1 B), as shown in the figure from left to right are T, S1+S2+S3, S1+S2, S1, S1+pS2, S1+pS2+pS3, p3T, and pb* (b*-BBP) in the red dashed box. At the same time, BBP was labeled with FITC, and green fluorescence expression of the corresponding band was observed at the same position. The stable connection between the polypeptide and the nucleic acid backbone was also verified by high-performance capillary electrophoresis (HPCE) ( Figure 1 C) After BBPs bind to tFNA, the total molecular weight increases significantly from nearly 210 bp of tFNA to nearly 280 bp of p3T.
[0126] In order to visually confirm the accurate synthesis of BBPs and tFNA in different ratios, the present invention uses Cy5 fluorescence (red) and FITC fluorescence (green) to label the S1 chain and BBP in the framework nucleic acid structure respectively. The co-localization results of yellow fluorescence confirm that BBPs are successfully loaded onto tFNA ( Figure 1 D). The four lanes from left to right represent T, p1T, p2T, and p3T, respectively. There is no significant difference in the relative intensity of red fluorescence, indicating that the concentrations of the four groups are consistent. While the relative intensity ratio of green fluorescence of p1T, p2T, and p3T is approximately 1:2:3, which is consistent with the precise binding ratio of the three groups of BBPs and tFNA.
[0127] Dynamic light scattering (DLS) was used to measure the hydrodynamic size and zeta potential. Figure 1E, F). p3T (26.60±6.01nm) showed a larger size compared to tFNA (15.96±3.05nm). Due to the positive charge of BBPs, p3T (-4.18±2.34mV) had less negative charge than tFNA (-13.78±4.31mV).
[0128] To observe their morphological characteristics, transmission electron microscopy (TEM) and atomic force microscopy (AFM) were used to analyze tFNA and p3T, respectively. Figure 1 G, H). Both TEM and AFM images show that p3T presents a tetrahedral structure with three chains at the top, and is evenly dispersed and uniform in size (about 30 nm). This further clarifies the morphology of p3T and is consistent with the DLS results.
[0129] The present invention uses agarose gel electrophoresis (AGE) to conduct drug serum stability experiments and enzyme stability experiments. Figure 1 As shown in Figure 1, at 37°C and in the presence of 1U / mL DNase I, p3T gradually degrades over time, but its band can still be retained for 12 hours. In order to simulate the in vivo environment and ideal cell growth conditions, the present invention further studies the degradation curve of p3T over time in 10% FBS, 5% FBS and fetal bovine serum-free environments. Figure 1 As shown in J-1L, based on the detected gelred signal and Cy5 fluorescence signal, it can be seen that under the incubation conditions of 10% FBS, the band showed signs of degradation after 6 hours; in the presence of 5% FBS, p3T remained stable for up to 9 hours; and at room temperature in the absence of serum, p3T showed high stability, which was maintained for at least 7 days.
[0130] In summary, the present invention successfully chemically linked the polypeptide to a single-stranded DNA of a specific sequence, and further synthesized a stable framework nucleic acid-polypeptide structure p3T, providing a theoretical basis for its effective biological function.
[0131] 2. Characterization of BBPs-tFNA modified HAMA scaffold
[0132] Figure 2 A is a schematic diagram of the preparation of BBPs-tFNA modified HAMA scaffold. Scanning electron microscopy (SEM) analysis showed that the functionalized hydrogel scaffold had a porous structure ( Figure 2 B). In order to detect the mechanical properties of the cured gel structure, the present invention conducted rheological and compression characteristics analysis ( Figure 2C). The results show that under the changes of time and temperature (i&iv), the storage modulus (G') of the composite hydrogel is stably greater than the loss modulus (G"), indicating that its stable gel-like structure has good mechanical strength. Moreover, both the stress-strain curve (ii) and the stress-ω curve (iii) show that the composite hydrogel structure can withstand large mechanical stress and maintain stable elastic properties.
[0133] Subsequently, liquid nuclear magnetic resonance (NMR, Figure 2 D) and X-ray photoelectron spectroscopy (XPS, Figure 2 F) measurements were used to evaluate the occurrence of chemical modifications in p3T-functionalized HAMA hydrogel scaffolds (HA-p3T). The NMR measurements showed chemical shifts of hydrogen bonds in adjacent positions of CS, and the XPS spectra and full spectrum analysis data showed the formation of specific CS bonds in HA-p3T materials. Furthermore, the changes in the surface wettability of the composite hydrogel material were verified by water contact angle measurements ( Figure 2 E). The results showed that although both hydrogel materials showed good hydrophilicity, the wettability of HA-p3T hydrogel was 12.34°±0.60°, which was less than that of HAMA hydrogel (15.11°±0.66°) (p<0.0001), indicating that p3T was chemically connected and fixed in HAMA hydrogel.
[0134] To verify the stability of this chemical connection, the present invention compared the elution of HAMA hydrogels physically adsorbed with BBPs. Figure 2 G, Figure 2 As shown in Figure H, after four large-scale washes, different high concentrations of BBPs-FITC were obviously eluted, but the hydrogel modified with the chemically bound peptide-nucleic acid framework structure did not show obvious fluorescence decay (p>0.05). Quantitative statistical results also verified this phenomenon.
[0135] Therefore, the certain mechanical strength of HAMA and its chemical connection form with BBPs-tFNA are conducive to the stable biological efficacy of the scaffold, providing feasibility for realizing the capture ability of specific proteins.
[0136] 3. Efficacy of BBPs-tFNA-functionalized HAMA in enriching BMP-2
[0137] In order to verify the affinity and specificity of BBPs-tFNA binding to BMP-2 in vitro, polyacrylamide gel electrophoresis (PAGE) was used to compare the binding amount of BBPs-tFNA after incubation with equal concentrations of rhBMP-2 and FBS for 1 hour. Figure 3As shown in A, p1T, p2T, and p3T can all bind to rhBMP-2. And because the molecular weight increases after binding to large molecular proteins, lighter bands are observed at the corresponding original BBPs-tFNA positions. According to the comparison of retention and original band signal intensity, the binding efficiency of p1T, p2T, and p3T with rhBMP-2 increases in turn, and p3T can reach 72.95%±4.08%. However, p1T, p2T, and p3T did not show obvious binding activity with protein-rich FBS, and their binding rate was less than 5%. Similarly, tFNA did not show affinity with either rhBMP-2 or FBS.
[0138] Furthermore, the present invention uses a green fluorescent reGFP protein with a size similar to rhBMP-2 to verify the specificity of HA-p3T binding to BMP-2. The data show ( Figure 3 B), p3T with cy5 fluorescence label was not eluted after chemical connection to HAMA (p>0.05), but both HA and HA-p3T were eluted in large quantities after incubation with 1μg / mL reGFP for 1 hour, leaving little green fluorescence signal (p<0.0001), which proved that HA-p3T did not show binding affinity to reGFP.
[0139] In contrast, HA and HA-p3T scaffolds were incubated with 1 μg / mL rhBMP-2 solution for 1 hour and washed extensively before rhBMP-2 immunostaining qualitative analysis to determine the specific binding of HA-p3T to rhBMP-2. The results showed ( Figure 3 C), the maximum fluorescence intensity was observed only when the HA-p3T scaffold was incubated with rhBMP-2 (p<0.0001). The amount of rhBMP-2 captured and retained on the scaffold was quantified using ELISA ( Figure 3 D), the results of the present invention show that when BBPs-tFNA is present, the HAMA hydrogel scaffold captures more rhBMP-2, which is consistent with the results of immunofluorescence staining. Among them, the capture efficiency of HA-p3T is as high as 89.14% ± 4.24%, which is statistically different from HA-p1T (78.24% ± 1.48%) and HA-p2T (83.05% ± 1.58%). However, the capture efficiency of HA and HA-T is much lower than that of the HAMA scaffold functionalized with BBPs-tFNA. And there is no statistical difference in capture efficiency between the HA and HA-T groups (P = 0.1953).
[0140] In addition, in order to explore the effect of the tetrahedral structure on the capture efficiency, the present invention compared the BBP and DNA single-stranded connection form (pS) with the p3T structure, and modified HAMA at a ratio of 3:1 to obtain HA-3pS. Figure 3 E(i) and confirmed that HA-3pS and HA-p3T had consistent BBP content at the same synthesis concentration, and there was no statistical difference. Figure 3 E(ii) The results showed that HA-p3T could retain more rhBMP-2 on the scaffold and had a higher capture efficiency (p<0.0001) than HA-3pS of the same concentration. This indicated that compared with HA-3pS, HA-p3T prepared by a specific method had a significantly higher rhBMP-2 capture efficiency (p<0.0001) at the same BBP content, achieving an unexpected technical effect.
[0141] The present invention investigates the capture strength of HA-p3T treated with rhBMP-2 solutions of different concentration gradients. Figure 3 F shows that with the increase of concentration, the efficiency of HA-p3T scaffold binding to rhBMP-2 is gradually increasing, reaching the highest efficiency at a concentration of 1 μg / mL. When treated with rhBMP-2 concentrations higher than 1 μg / mL, the retention efficiency of HA-p3T is slightly reduced (p>0.05). Therefore, 1 μg / mL of rhBMP-2 was selected as the condition for treating HA-p3T in in vitro experiments. In order to simulate cell culture conditions, the present invention further explored the release curve of HA-p3T scaffold treated with rhBMP-2 in 10% FBS ( Figure 3 G) The results showed that rhBMP-2 bound to the HA-p3T scaffold was continuously released within 72 hours, and the release rate of BMP-2 reached 97.59%±1.09% within 72 hours.
[0142] In summary, the high affinity and specific binding of BBPs to rhBMP-2 and the topological spatial conformation of trivalent ligand binding provided by p3T help the HA-p3T scaffold to efficiently capture and fix BMP-2 in vitro and in vivo.
[0143] 4. Bioactivity Verification of BMP-2 Enriched in HA-p3T Scaffold
[0144] The present invention uses rat-derived bone marrow-derived mesenchymal stem cells (BMSCs) to study the biocompatibility of HA-p3T and its osteogenic differentiation activity under the influence of BMP-2 captured by the HA-p3T scaffold.
[0145] First, the cell counting kit-8 (CCK-8) assay was used to evaluate the effects of each group on the cell activity and proliferation of BMSCs at different time points ( Figure 4A). The results showed that although the cell activity decreased slightly with the increase of culture time, more than 90% of the cells survived within the 72-hour culture period, and there was no significant difference between the groups at 12 hours, 48 hours and 72 hours. The 24-hour data showed that the survival rate of cells on HA-T and HA-p3T scaffolds was slightly higher (P<0.05), indicating that the two groups may have slightly promoted cell growth. Consistent with the results of the CCK-8 experiment, the live-death experiment ( Figure 4 B) shows that there was no significant difference in the number of cells in each group after 72 hours of co-culture (p>0.05). The number of cells in the group with HAMA was slightly higher than that in the control group. The above results show that HAMA has good biocompatibility, and the modification of tFNA and p3T has little effect on the growth of BMSCs on the scaffold.
[0146] In the present invention, the hydrogel scaffold was co-cultured with the rhBMP-2 solution under the above conditions and washed in large quantities, and then transplanted into the upper layer of the cell culture chamber to further explore the osteogenic differentiation effect and mechanism of the effective components continuously released by the hydrogel scaffold through the microporous membrane on the BMSCs in the lower layer ( Figure 4 H).
[0147] It is known that BMP-2 can induce BMSCs to differentiate into osteoblasts, and alkaline phosphatase (ALP) is one of the characteristic markers of early osteogenic differentiation. Therefore, the present invention uses a BCIP / NBT alkaline phosphatase colorimetric kit to detect the activity of ALP 7 days after BMSCs are implanted. Figure 4 The staining image of C shows that the HA-p3T scaffold treated with rhBMP-2 solution showed more ALP-positive cells (purple), similar to the positive control group incubated with the same concentration of soluble rhBMP-2. Consistent with the staining results, quantitative measurements showed that ( Figure 4 E), the ALP activity expressed by BMSCs cultured in the HA-p3T scaffold preloaded with rhBMP-2 (HA-p3T+BMP-2 group) was significantly higher than that in the untreated group (HA-p3T group) before cell inoculation (p<0.0001). However, HA and HA-T scaffolds, whether pretreated with rhBMP-2 or not, did not show significant ALP activity (p>0.05), which indirectly demonstrated that HA and HA-T scaffolds did not show the ability to specifically capture and fix BMP-2.
[0148] In addition, calcium nodules are considered to be an important late marker of osteogenic differentiation of mesenchymal stem cells. Therefore, in order to further explore the late effect of promoting osteogenic differentiation of BMSCs under the influence of HA-p3T scaffolds preloaded with rhBMP-2, the present invention used Alizarin red to stain the calcium nodules secreted by osteoblasts after 15 days of osteogenic induction ( Figure 4D) The results showed that the staining of the HA-p3T+BMP-2 group and the positive control group was stronger than that of the other groups, indicating the presence of more calcium salts or calcium nodules. Further semi-quantitative analysis of the mineralized nodules formed was performed. Figure 4 The results of F showed that the relative mineralization levels of the HA-p3T group preloaded with rhBMP-2 and the positive control group were much higher than those of the other groups, which was consistent with the results of ALP enzyme activity detection.
[0149] The effective ingredient BMP-2 continuously released in the HA-p3T capture system has a certain effect on the expression of early and late osteogenic differentiation markers of BMSCs. In order to further confirm its effect on the osteogenic differentiation ability of BMSCs, the present invention detected the expression levels of osteogenic differentiation-specific genes in different treatment groups after 1 week and 2 weeks of co-culture. Among them, ALP, Runx2, and OSX are marker genes for early osteogenic differentiation, while BSP and OPN represent the middle and late stages of osteoblast differentiation. In addition, the study also confirmed the key role of Runx2 and OSX gene expression in BMP-2-induced differentiation of bone marrow mesenchymal stem cells into osteoblasts.
[0150] like Figure 4 As shown in G, after 1 and 2 weeks of treatment with HA-p3T that specifically binds to rhBMP-2, the expression of the above-mentioned specific osteogenic differentiation genes was significantly upregulated, which was significantly higher than that of the control group and the HA and HA-T treatment groups that nonspecifically adsorbed rhBMP-2, and there was no statistical difference compared with the positive control group treated with rhBMP-2.
[0151] In addition to detecting BMSCs osteogenic differentiation-related genes, the present invention also detected the expression levels of corresponding osteogenic differentiation-related proteins by western blot (WB) and immunofluorescence techniques. Figure 5 As shown in A, the expression levels of ALP, Runx2, OSX, and OPN proteins in the HA-p3T scaffold group and BMP-2 group were significantly enhanced and higher than those in the other three groups. Statistical analysis further confirmed this conclusion ( Figure 5 B). The expression levels of Runx2 and OSX proteins in the HA-p3T scaffold group were slightly lower than those in the positive control group. In addition, laser confocal microscopy ( Figure 5 C, D), the fluorescence signals of ALP, Runx2, OSX, and OPN detected in the HA-p3T scaffold group were significantly stronger than those in the control group, HA and HA-T groups, and there was no significant difference in intensity with the above-mentioned positive control group. Further statistical analysis was consistent with the conclusion of RT-qPCR.
[0152] In summary, the capture system constructed by the present invention can continuously release effective BMP-2 components in the BMSCs culture environment, promote the osteogenic differentiation of BMSCs, and significantly upregulate the expression of osteogenic differentiation-specific proteins and genes.
[0153] 5. Efficacy of HA-p3T scaffolds in capturing endogenous BMP-2
[0154] Studies have shown that BMP-2 plays an important role in the early bone formation process. In order to evaluate the early capture efficiency of HA-p3T, the present invention first performed in vivo real-time imaging. The p3T-modified HAMA scaffold and the S2 chain-modified HAMA scaffold were implanted subcutaneously ( Figure 6 A). The results showed that the Cy5 signal was still obvious in the first 10 days after HA-p3T was implanted in situ, and the fluorescence intensity slowly decreased. Meanwhile, the fluorescence signal of the HA-ss group was rapidly depleted within 3 days, indicating that its stability was significantly lower than that of the HA-p3T group. Therefore, the HA-p3T scaffold has good structural stability and local retention ability in vivo, which provides support for its early capture of BMP-2.
[0155] The present invention constructs a rat skull defect model and places the preformed HA-p3T scaffold at the defect site in order to achieve the purpose of early capture of endogenous BMP-2, osteogenic induction and bone defect repair ( Figure 6 B) First, an ELISA experiment was used to quantitatively analyze the amount of BMP-2 captured by different scaffold materials in vivo. Figure 6 C capture curve results, each treatment group was detected with a much higher amount of BMP-2 than the blank control group (sham group). Among them, the amount of BMP-2 specifically captured by the HA-p3T scaffold was significantly higher than that of the other groups. As time went by, the amount of BMP-2 captured on the HA-p3T scaffold gradually increased, reaching the highest on the seventh day and then slightly decreasing. The amount of BMP-2 captured on the seventh day was statistically analyzed ( Figure 6 D), there was no significant difference between the HA group and the control group, further confirming that the HA scaffold had no targeted capture effect of endogenous BMP-2.
[0156] The present invention qualitatively analyzed the BMP-2 protein expression levels in the bone end tissues of different treatment groups one week after bone defect by immunofluorescence, and compared them with the blank group ( Figure 6 E). The maximum fluorescence intensity was observed in the HA-p3T group, and the relative expression of BMP-2 captured by it was significantly stronger than that of the other three groups (p<0.0001). Further statistical analysis ( Figure 6 F) is consistent with the above quantitative detection results. Next, the present invention uses immunohistochemistry to analyze whether the early bone remodeling in the HA-p3T group is caused by the capture of endogenous BMP-2 by the functionalized hydrogel scaffold. In the second week after skull defect reconstruction, positive expression of BMP-2 protein was observed in the tissue surrounding the bone defect ( Figure 6 G). The relative positive area of each group was statistically analyzed ( Figure 6H), the content of BMP-2 in the bone matrix and connective tissue around the defect in the HA-p3T group was much higher than that in the other groups.
[0157] The above results indicate that the p3T-functionalized bioscaffold material HA-p3T can achieve specific and large-scale capture of endogenous BMP-2 in the early stage of bone defect, which is expected to promote early bone formation and accelerate bone defect healing.
[0158] 6. HA-p3T captures endogenous BMP-2 to promote bone remodeling
[0159] To verify the efficacy of endogenous BMP-2 captured by HA-p3T scaffolds in promoting in situ bone regeneration, Micro-CT was used to monitor osteogenesis in the bone defect area. Figure 7 As shown in A, the control group and the HA scaffold group had the least growth of new bone tissue, and the skull defect was still clearly visible after two months. The HA-p3T scaffold group showed the largest proportion of new bone tissue in the region of interest at both one and two months. The bone volume / total volume (BV / TV), bone mineral density (BMD), trabecular thickness (Tb.Th), total number of trabeculae (Tb.N) and trabecular spacing (Tb.Sp) at the skull defect were further quantitatively analyzed ( Figure 7 B and 7J). The results showed that the HA-p3T scaffold group had the highest expression of BV / TV, BMD, Tb.Th and Tb.N in the region of interest, while the expression of Tb.Sp was the lowest at one month and two months, all with significant statistical differences (p<0.001). This proved that the HA-p3T scaffold group had a better bone defect repair and healing effect than the other groups.
[0160] In addition, HE and Masson staining results further emphasized the potential of HA-p3T in bone regeneration ( Figure 7 C and 7D). Among them, inflammatory cells, thin connective tissue and collagen fibers were observed in the defect sites in both the control group and the HA group, and a small amount of osteoid was formed. The HA-p3T scaffold group showed significant new bone formation and increased bone density after 1 month and 2 months of bone defect compared with the other two groups. In the HA-p3T scaffold-treated group, it can be observed that the fracture line of the defect end is blurred after 2 months, indicating a good osteogenesis effect. Masson staining also supplemented that the collagen fiber content in the bone defect area after HA-p3T scaffold treatment increased significantly after 1 month and 2 months.
[0161] In order to further evaluate the effectiveness of HA-p3T in promoting bone regeneration and repair, the present invention performed tissue immunofluorescence staining to detect the expression levels of specific proteins related to bone tissue development. Type I collagen (Col-I) and Runx2 are believed to play a key role in BMP-2-induced osteogenic differentiation and bone formation. Therefore, the present invention confirms the specific advantages of HA-p3T in stimulating bone regeneration and repair by detecting the relative expression levels of Col-I and Runx2. Compared with the control group and the HA scaffold group, the HA-p3T group showed significantly higher levels of osteogenic specific proteins, namely Col-I and Runx2 ( Figure 7 E and 7F). At the same time, quantitative statistical analysis of relative fluorescence intensity further confirmed the significant differences in the above protein levels ( Figure 7 H). In addition, osteocalcin (OCN) is considered a typical late osteogenic differentiation marker. Further immunohistochemical analysis confirmed that the application of HA-p3T scaffolds significantly enhanced the expression of OCN in the bone defect site after 1 month and 2 months ( Figure 7 G and 7I). In contrast, the bone matrix and connective tissue around the defect in the control and HA groups showed lower OCN expression signals, and the difference was statistically significant.
[0162] Therefore, the HA-p3T scaffold with the ability to specifically capture endogenous BMP-2 can efficiently promote bone regeneration and reconstruction, and ultimately accelerate the bone healing process after bone defects, confirming that HA-p3T is a better candidate for potential clinical application in bone defect repair.
[0163] In summary, the present invention provides a DNA tetrahedron-based complex and its preparation method and use. The present invention designs a bioactive composite hydrogel scaffold modified with a functionalized DNA tetrahedron complex containing BMP-2, stably combines a functionalized BMP-2 binding peptide with a tetrahedral framework structure having a unique three-dimensional spatial structure and refined programmability by chemical click, and then further prepares a composite hydrogel scaffold with methacryloyl hyaluronic acid (HAMA). A strategy for fixing BMP-2 by specifically and highly affinity binding with a BMP-2 binding peptide is proposed, and the performance of the functionalized DNA tetrahedron complex to efficiently capture BMP-2 in an ordered and stable topological spatial conformation is achieved. The functionalized composite hydrogel scaffold achieves targeted capture of endogenous BMP-2 in the early stage of bone defects and stimulates osteogenic differentiation of stem cells to promote in situ osteogenesis, avoiding the occurrence of a series of complications caused by the delivery of exogenous bone morphogenetic protein-2, poor in vivo stability, safety issues and high cost issues, and has good application prospects.
Claims
1. A composite hydrogel, characterized in that: The invention is obtained by mixing and curing a BMP-2-binding peptide-modified DNA tetrahedron complex, a hydrogel monomer and a photoinitiator.
2. The composite hydrogel according to claim 1, characterized in that The mass of the hydrogel monomer accounts for 0.5-1.5wt.% of the total mass of the BMP-2 binding peptide modified DNA tetrahedral complex and the hydrogel monomer; the molar ratio of the BMP-2 binding peptide modified DNA tetrahedral complex to the photoinitiator is 1:200-300×10 3 .
3. The composite hydrogel according to claim 2, characterized in that The mass of the hydrogel monomer accounts for 1wt.% of the total mass of the BMP-2 binding peptide modified DNA tetrahedral complex and the hydrogel monomer; the molar ratio of the BMP-2 binding peptide modified DNA tetrahedral complex to the photoinitiator is 1:255×10 3 .
4. The composite hydrogel according to claim 1, characterized in that In the BMP-2 binding peptide modified DNA tetrahedron complex, the BMP-2 binding peptide modifies 1 to 3 single strands in the DNA tetrahedron.
5. The composite hydrogel according to claim 4, characterized in that In the BMP-2 binding peptide modified DNA tetrahedron complex, the BMP-2 binding peptide modifies three single strands in the DNA tetrahedron.
6. The composite hydrogel according to claim 5, characterized in that The BMP-2 binding peptide modified DNA tetrahedron complex is self-assembled by SH-S1, bS2, bS3, bS4, and b*-BBP single chains; SH-S1 is a thiol-modified S1 single chain, and b*-BBP is a propargyl-modified BBP that reacts with an azide-modified sticky end under the action of a catalyst, and is purified to obtain; The S1 sequence is shown in SEQ ID NO.2, and the sequences of bS2, bS3, bS4, BBP and sticky ends are shown in SEQ ID NO.6, SEQ ID NO.7, SEQ ID NO.8, SEQ ID NO.1 and SEQ ID NO.9, respectively.
7. The composite hydrogel according to any one of claims 1 to 6, characterized in that The hydrogel monomer is methacrylated hyaluronic acid; the photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.
8. A method for preparing the composite hydrogel according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing the BMP-2 binding peptide-modified DNA tetrahedron complex, hydrogel monomer and photoinitiator, and curing to obtain the product.
9. The method according to claim 8, characterized in that The curing wavelength is 350-400 nm, preferably 365 nm; the curing time is 20-40 seconds, preferably 30 seconds.
10. Use of the composite hydrogel according to any one of claims 1 to 7 in preparing a biological scaffold material for repairing bone defects.
Citation Information
Patent Citations
A bone regeneration material having a cotton-wool like structure formed of a plurality of electrospun fibers
CN113226386A
Programmable DNA tetrahedral nano device for early diagnosis of acute kidney injury as well as preparation method and application of programmable DNA tetrahedral nano device
CN114414544A
DNA tetrahedron-based compound and scaffold material for stem cell enrichment
CN118440936A
Non-dendritic backbone piptide carrier
CN1215404A
Bone Morphogenic Protein Binding Peptide
US20080241108A1
Cited By
Tacrolimus and siRNA combined double-drug-loading microneedle as well as preparation method and application thereof
CN120241771A